THE EXPERIENCE OF ORGANIZING TRAINING FOR FOREIGN STUDENTS OF THE FIRST YEAR OF MEDICAL BIOLOGY - Фрич, Н. І.; Довганич, Н. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The article summarizes the teaching experience of Medical biology to first-year students (English-speaking and Russian-speaking) of the Ivano-Frankivsk National Medical University. The main problems that determine the level of adaptational possibilities of foreign students to the educational process are outlined: language barrier, low level of knowledge and low level of points in basic disciplines at the pre-university stage, demotivation to the subject. According to the teaching experience of Medical biology, these problems are overcoming due to such steps. First of all, all educational and methodological materials on the discipline "Medical biology" were created and adapted, manuals for Russian-speaking and English-speaking students were prepared for a deep and full understanding of the material presented. Secondly, in order to form an internal motivation to study, an individual approach to each student was found. To optimize the educational process, the introduction of materials is intensified and innovative methods are used. To improve adaptability of foreigners to the curricula of different countries advisory days were organized. Foreign students encourage to the participation of the experimental researches in the laboratory.